Mind the gap: TB trends in the USA and the UK, 2000–2011. Issue 4 (23rd February 2016) - Nnadi, Chimeremma D; Anderson, Laura F; Armstrong, Lori R; Stagg, Helen R; Pedrazzoli, Debora; Pratt, Robert; Heilig, Charles M; Abubakar, Ibrahim; Moonan, Patrick K
Abstract : Background: TB remains a major public health concern, even in low-incidence countries like the USA and the UK. Over the last two decades, cases of TB reported in the USA have declined, while they have increased substantially in the UK. We examined factors associated with this divergence in TB trends between the two countries. Methods: We analysed all cases of TB reported to the US and UK national TB surveillance systems from 1 January 2000 through 31 December 2011. Negative binominal regression was used to assess potential demographic, clinical and risk factor variables associated with differences in observed trends. Findings: A total of 259 609 cases were reported. From 2000 to 2011, annual TB incidence rates declined from 5.8 to 3.4 cases per 100 000 in the USA, whereas in the UK, TB incidence increased from 11.4 to 14.4 cases per 100 000. The majority of cases in both the USA (56%) and the UK (64%) were among foreign-born persons. The number of foreign-born cases reported in the USA declined by 15% (7731 in 2000 to 6564 in 2011) while native-born cases fell by 54% (8442 in 2000 to 3883 in 2011). In contrast, the number of foreign-born cases reported in the UK increased by 80% (3380 in 2000 to 6088 in 2011), while the number of native-born cases remained largely unchanged (2158 in 2000 to 2137 in 2011). In an adjusted negative binomial regression model, significant differences in trend were associated with sex, age, race/ethnicity, site of disease, HIV status and previous history of TB (p<0.01). Among the foreign-born, significant differences in trend were also associated with time since UK or US entry (p<0.01). Interpretation: To achieve TB elimination in the UK, a re-evaluation of current TB control policies and practices with a focus on foreign-born are needed. In the USA, maintaining and strengthening control practices are necessary to sustain the progress made over the last 20 years.